Engineered in vivo and in vitro tumor model recapitulates vasculogenic mimicry signatures in melanoma - Qizhi Shuai; Xinrui Xu; Yuxiang Liang; Zulala Halbiyat; Xin Lu; Zixuan Hu; Zhiwei Peng; Jie An; Zhiwei Feng; Tingjuan Huang; Hong Zhao; Zhizhen Liu; et al. (Bioengineering & Translational Medicine, 2024)
Abstract Vasculogenic mimicry (VM) describes a process by which tumor cells formed a novel microcirculation pattern in an endothelial cell‐free manner. Clinically, VM is associated with aggressive phenotype and poor patient survival. However, the current models for investigating VM include 2D monolayer cultures, Matrigel‐based cultures, and animal models, each of which has limitations. Matrigel‐based models often exhibit batch‐to‐batch variations, while in vivo tumor models currently produce insufficient amounts of VM. There is currently no suitable tumor model to discover new therapeutic targets against VM. Herein, we establish an extracellular matrix (ECM)‐based engineered tumor model in vivo and in vitro. In this study, we demonstrate that matrix proteins enhanced the VM formation in the engineered xenograft model. Furthermore, we also investigated the role of collagen/fibronectin (FN) in melanoma progression and VM formation. Compared with cells cultured on TCPS plates, the B16F10 cells cultured on collagen/FN coated plates showed increased proliferation and stemness, and significantly enhanced invasion and formation of VM networks. Molecular mechanism analysis showed that Integrin/VE‐cadherin/EphA2/PI3K/MMP‐2 signaling pathways are responsible for VM formation. Our results indicate that collagen/FN matrix plays an important role in VM formation in melanoma, suggesting that ECM protein is a potential therapeutic target for anti‐VM therapy for melanoma.